A Medico-Legal Study on the Use of Infant Formula as an Alternative to Breastfeeding for Children Aged 0–2 Years - Widiastuti, W.; Ropii, Imam; Carolina (Manunggal Halim Jaya, 2025)
The significant gap between the recommendation for exclusive breastfeeding and its implementation in practice—where many infants still receive formula milk without clear medical indications—highlights the need for more comprehensive regulations and medicolegal oversight to safeguard the health rights of children aged 0–2 years. This study aims to analyze the legal framework and medicolegal aspects of using formula milk as an alternative to breastfeeding for children in this age group. Using a normative legal research method, the study employs statutory, conceptual, and historical approaches, drawing on primary and secondary legal sources, including relevant laws and government regulations. The findings reveal that although national rules, such as Law No. 17/2023 on Health and Government Regulation No. 28/2024, affirm the right to exclusive breastfeeding and restrict formula use to medical indications, gaps remain in implementation and understanding among healthcare professionals. The use of formula milk is permitted only when there is a medical indication, with priority given to donor breast milk. In such cases, formula use must meet AFASS (Acceptable, Feasible, Affordable, Sustainable, and Safe) criteria, be supported by written parental consent, and adhere to strict health protocols. This research contributes to the discourse on child protection, health law, and ethical medical practice, while encouraging the development of stronger operational policies and public education on the responsible use of formula milk based on children's rights and public health safety.